Avaliação do potencial antimicrobiano de Eplingiella fruticosa, Gymneia platanifolia e Medusantha martiusii (Lamiaceae) contra micro-organismo de interesse agrícola - Santos, Uiliane Soares dos (2016)
The cultures of vine and tomato have an important economic role in Brazil. However phytosanitary issues can compromise the productivity of crops, one issue which stands out are diseases caused by fungi and bacteria that result in immeasurable harm to farmers. Considering the economic, environmental impact and health of the population resulting from the massive use of pesticides it is extremely important that there as studies done to find an alternative control of diseases, such as the use of natural products with antimicrobial activity. Plant extracts and essential oils appear as potential alternatives that can be incorporated into management of phytopathogens, since they can be highly volatile and low persistence, which results in less contamination of the environment. In this context, the Lamiaceae family species is notable for presenting important biological activities, among them high antimicrobial activity. Based on the above, the present study aimed to evaluate the antimicrobial activity of methanol extract and essential oils of species of Eplingiella fruticosa (Salzm. Ex Benth.) Harley & J.F.B.Pastore, Gymneia platanifolia (Mart. ex Benth.) Harley & J.F.B.Pastore and Medusantha martiusii (Benth.) Harley & J.F.B.Pastore against bacteria as Xanthomonas campestris pv. viticola (Naydu) Dye e Ralstonia solanacearum (Smith), causing bacterial canker of grapevine and tomato bacterial wilt, respectively, and fungi causing rots post-harvest vine Aspergilus niger Van Tieghem, Cladosporium herbarum (Pers.:Fr.) Link, Lasiodiplodia theobromae (Pat.) Griffon & Maubl e Rhizopus sp. The plant species were harvested at Feira de Santana, BA. The collected material (leaves) after drying at ambient temperature, were used for the preparation of the extracts (crude methanol), and the extraction of essential oils. The chemical constituents of essential oils were quantified and identified through the techniques of GC/FID and GC/MS. To check the antibacterial activity of extracts and essential oils the diffusion method in agar by the method of discs was used. These were impregnated with essential oils and extracts at different concentrations. The variable studied was the halo diameter of bacterial growth inhibition. For the verification of the minimum inhibitory concentration (MIC) of the extracts and oils microdilution broth method were used. For the evaluation of the antifungal activity diffusion on agar method was used. The methanol extracts and essential oils were incorporated into the PDA culture at different concentrations. The variable analyzed was the diameter of the mycelial growth. The data were submitted to analysis of variance and their means compared by Scott-Knott test at 5% probability of error and the analysis concentrations of regression. According to the obtained results can infer that the methanolic extracts and essential oils of Eplingiella fruticosa, Medusantha martiusii and Gymneia platanifolia species showed antibacterial activity against bacteria X. campestris pv. viticola and R. solanacearum, in two concentrations and MICs ranging from 125 µL mL-1 to 1000 µL mL-1, with a strong to moderate antibacterial activity. The methanol extracts and essential oils studied have antifungal activity against phytopathogens such as Aspergilus niger, Cladosporium herbarum, Lasiodiplodia theobromae and Rhizopus sp.